Electrochemical technologies for hydrogen powered vehicles - A. A. Filimonova; A. A. Chichirov; N. D. Chichirova; R. I. Razakova (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. Consider the electrochemical technologies used for the production of hydrogen at gas stations and the operation of hybrid electric vehicle engines on storage batteries with fuel cells. Comparative analysis of the production and use of energy by electrochemical and traditional methods in vehicles. METHODS. Based on the analysis of literature data and mathematical calculations. RESULTS. For a light electric vehicle, the calculation of the amount of electricity that can be obtained in a fuel cell by processing 1 kg of hydrogen was carried out. It has been shown that a hydrogen electric car can travel about 100 km for 1 kg of hydrogen. A comparison was made of the fuel costs for different types of automotive engines for the current market conditions in Russia and the EU countries. CONCLUSION. Hydrogen can become the environmentally friendly fuel of the future, reduce global dependence on fossil fuel resources and reduce carbon dioxide emissions from the transportation industry. Today, green technologies have made significant progress, modern vehicles of various classes on hydrogen fuel have been developed and sold around the world, and their price characteristics are already comparable to existing traditional technologies. The advantages of electrochemical technologies for the production and use of hydrogen in the road transport sector are sufficient to make hydrogen a serious energy candidate for modern transportation systems.